Effect of Biostimulators on the Productivity Indicators of Mulberry Silk Cow - Tukhtamuradovich, Daniyarov Umirzak; Jo‘rayeva, Sh. A. (American Journal of Botany and Bioengineering, 2024)
By enriching the leaves of the mulberry silkworm hybrids grown for industrial purposes with 0.001% mulberry leaf (AIH-10) in the IV-V years, it was possible to increase the average cocoon weight, which is one of the silkworm productivity indicators, to 1.80 grams, by 7.3% compared to the cocoons of the comparative variant (1.67 g), the cocoon shell weight to 42 mg, and the silkiness to 0.8%.